1997
DOI: 10.1620/tjem.182.207
|View full text |Cite
|
Sign up to set email alerts
|

EMG Power Spectrum and Integrated EMG of Ankle Planterflexors during Stepwise and Ramp Contractions.

Abstract: The aim of this study was to investigate whether the median frequencies (MF) of the electromyogram (EMG) and the integrated EMG (IEMG) of histochemically differentiated ankle plantarflexors, the gastrocnemius and soleus, were force dependent. Bipolar intramuscular wire electrodes were used to measure EMG of the soleus (SO), medial head of gastrocnemius (GM), and lateral head of gastrocnemius (GL) during ramp (single ongoing contractions) with the force increasing linearly from 0 to 100% of maximum voluntary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 30 publications
4
19
0
Order By: Relevance
“…As was reported by some authors [4,20], using the Glazer Protocol in the evaluation of pelvic floor muscles related functional disorders, e.g. urinary incontinence, pelvic pain, or sexual disorders it is possible to observe the shifts to the left in sEMG median frequency.…”
Section: Protocolmentioning
confidence: 73%
See 1 more Smart Citation
“…As was reported by some authors [4,20], using the Glazer Protocol in the evaluation of pelvic floor muscles related functional disorders, e.g. urinary incontinence, pelvic pain, or sexual disorders it is possible to observe the shifts to the left in sEMG median frequency.…”
Section: Protocolmentioning
confidence: 73%
“…They have concluded that pelvic floor muscles training with sEMG biofeedback may influence mainly the bioelectric signal spectral frequency. Therefore the improvement in muscles contractile capabilities visible as changes in sEMG spectral frequencies may lead to pelvic floor muscles functional improvement [20].…”
Section: Protocolmentioning
confidence: 99%
“…Moreover, unlike the SO, a monoarticular muscle, the GM and GL are biarticular ones that cross the knee joint, hence the angle of the knee joint affects their contributions to plantar flexion torque. In addition to these difference, our previous study suggests that GL may have greater proportion of fast-fatigable twitch muscle fibers than GM 10) . Given these differences in the triceps muscles, their strategies in voluntary movements may differ [11][12][13][14] .…”
mentioning
confidence: 83%
“…However, the increase in the IEMG value is commonly believed to due to increases in the amplitude and density of EMG signals resulting from the mutual influences of recruitment and firing rate. For this reason, many studies have used ramp contraction, defined as the generation of a single ongoing force from 0 to MVC 10,[21][22][23][24][25][26] . To our knowledge, however, there have been no investigations on the activities of the prime mover at ramp contractions of various durations under an isometric condition and variable muscle length conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation